Vocational high school students’ identity and investment in learning English in a rural area - Nur Annisa; Soni Mirizon; Sary Silvhiany (Studies in English Language and Education, 2023)
This study explored vocational high school (VHS) students’ identity and investment during their English learning in the class at a private VHS in a rural area. The aim of this study was to understand how student identity impacted their investment in learning English. This study also attempted to seek factors that influenced students’ investment in learning English. To answer the research questions of this study, the narrative method was applied. This study involved six students from a VHS. The data were collected through semi-structured interviews and focus group discussions which was used to explore learning English at the VHS. The results revealed that the students had different ideas about their English learning. They are learning English outside the classroom, English necessity for future career, reluctant in learning English, perspective on future self. This study also revealed that the participants’ investment in learning English was hindered by five factors such as teaching method, inconvenient classroom environment, lack of knowledge, family, peer support, and having a part time job. VHS students need support to encourage them to commit investing their time and effort in improving their English language skills. The implication of this study is the importance of teachers encouraging learners’ investment in order to achieve desirable learning outcomes.